Quantifying the effect of IMPEDE-FX packing rate and volume on pressure-normalized principal wall strain in an idealized 3D-printed aneurysm model - Baqir Kedwai, BHSc; Joshua Geiger, MD; Sam Najjar, BS; Joel Kruger, MD; Michael Richards, PhD; Chung Yeh, BS; Mary Dennehy, BS; Michael Stoner, MD; Doran Mix, MD (JVS - Vascular Science)
Background: This study aimed to quantify the nonbiologic effects of Shape Memory IMPEDE-FX embolization plug deployment rate and packing volume on pressure-normalized wall strain (ερ+¯/PP) of an idealized 3D-printed abdominal aortic aneurysm model. Methods: An endograft was deployed into an abdominal aortic aneurysm model and connected to an industry-validated hemodynamic simulator. Plugs were deployed into the excluded sac to packing volumes of 100%, 200%, 300%, and 400% under two conditions: (1) sequential and (2) immediate deployment. Axial ultrasound images were taken for each packing volume. Frame-to-frame displacements of the aneurysm wall were measured with ultrasound elastography over one cardiac cycle and normalized to the circuit's pulse pressure to calculate the mean principal strain (ερ+¯/PP). Results: In the 100% packing condition, ερ+¯/PP was +113% above baseline at 15 minutes. After sequential deployment to 400%, the ερ+¯/PP trended down to +43% above baseline. Immediate packing was associated with a greater ερ+¯/PP reduction than sequential packing. When packed immediately to 400%, the ερ+¯/PP was −6.7% below baseline. Conclusions: These modeling data suggest that an immediate deployment strategy and higher plug packing volumes are associated with lower ερ+¯/PP, which has been associated with decreased sac growth rates. Clinical Relevance: The present findings suggest that rapid, high-volume filling of IMPEDE-FX embolization plugs results in a reduction in wall ερ+¯/PP, independent of thrombus formation. Fully expanded embolization plugs in aggregate limit pulsatile aortic sac displacement likely contribute to a greater reduction in overall wall strain compared with low packing volumes. These findings may inform clinical application for this device, supporting a rapid and high-volume deployment strategy for greater reduction in ερ+¯/PP status post endovascular aneurysm repair.